Study od discontinuities localization in rock using acoustic emission - M-Ch. REYMOND; A. JAROSZEWSKA (Archives of Acoustics)
A slow failure process of Rothbach sandstone and schist from Beringen in Belgium was examined, with particular attention to fault plane localization. The samples of rock were tested under uniaxial compressive stress. Acoustic emission and strain were measured during loading. The data obtained show that the localization threshold of fault plane occurred at stress levels with substantial variability relative to the ultimate strength, depending on the degree of dilatancy and homogeneity of rock under test.